Inter-regional disparities in the level of socio-economic development in tribal sub plan (TSP) area of Rajasthan - Kohli, Anju; Jain, Hansa (1999)
The paper attempts to identify and explain the inter-regional disparities in the levels of socio-economic development of tribal sub plan (TSP) area of Rajasthan. With the help of statistical techniques, an attempt is made to categorise the whole TSP area on the basis of its levels of development. An attempt is also made to show the interdependency of the various sectors and their contribution in the development of the area. The study also highlights the main reasons of backwardness of the region so that policies could be framed accordingly. The study is entirely based on secondary data for the year 1991. - Reproduced
Keywords: Tribes - India - Rajasthan; Regional disparities - India - Rajasthan; Regional disparities